The effect of sucrose concentration on the transparency of solid soap-based cooking oil - Irda Handriani; Ika Kusuma Nugraheni; Mariatul Kiptiah (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram, 2022)
This research aimed to identify the effect of sucrose concentration on the transparency of solid soap and to analyze the quality of used cooking oil based on the pH standards of bath soap and the quality requirements of bath soap. Sucrose, a soaping agent, was concentrated at 0%, 7%, 9%, 11%, and 13%, for the test was carried out three times in a row. The test of solid soap was a test of soap transparency, pH, air content, amount of fatty acids, free alkali, free fatty acids, neutral fats, and mineral oil. The results showed that the concentration of sucrose in soap making greatly affected the transparency of soap. The most transparent is a soap with a concentration of 13% sucrose. The quality of soap based on used cooking oil against the pH standard of bath soap has met the standard, and the quality requirements of the Indonesian Nasional Standard for bath soap are appropriate except for the water content and the number of fatty acids.